Gender-Specific Correlates of Alcohol Use Among College Students in Kerala, India. Issue 4 (July 2020) - Raveendranathan, Dhanya; Jaisoorya, T. S.; Nair, B. Sivasankaran; Menon, Priya G.; Rani, Anjana; Thennarasu, K.; Murthy, Pratima
Background: Studies of alcohol use among college students in India have reported a male preponderance, but a recent large study suggested that alcohol use is increasing in young females. This increase in use among the young females is of concern as they experience poorer outcomes and a higher risk for addiction. Hence, we aimed to examine the gender-specific correlates of alcohol use among college students in the district of Ernakulum, Kerala. Methods: From 58 colleges, 5, 784 students completed a self-administered questionnaire that assessed use of alcohol, use of tobacco and illicit drugs, psychological distress, suicidality, symptoms of attention deficit hyperactivity disorder, and history of sexual abuse. Results: Of the questionnaires, 342 had incomplete responses and had to be discarded, and the rest (n = 5, 442, 94.1%) were analyzed. lifetime alcohol use was reported by 39% males and 12.6% females. In the multivariable logistic regression analysis using a full model, male students using alcohol compared to male non-users were older, non-Muslim, had poor academic performance, and used other substances. Female users, compared to female non-users, were non-Muslim, had urban residence, used tobacco, and had higher psychological distress, higher suicidal thoughts, and higher lifetime exposure to sexual abuse. Conclusion: Gender-specific differences extend across sociodemographic and psychological domains. Incorporation of these may improve the effectiveness of public health strategies addressing alcohol use.